Sediment resuspension in two adjacent shallow coastal lakes: controlling factors and consequences on phosphate dynamics - de Vicente, Inmaculada; Cruz-Pizarro, Luis; Rueda, Francisco J. (Aquatic sciences, 2010)
A combination of field measurements, modelling and laboratory experiments was used to evaluate the potential impact of sediment resuspension on phosphorus (P) dynamics. The study was carried out in two adjacent shallow coastal lakes (Lake Honda and Lake Nueva) which, due to their geographic proximity (only 200 m apart), are subject to equal meteorological forcing and represent ideal systems to study how morphometry and sediment properties relate to wind events. The focusing factors (a measure of the fluxes of sediment into the water column through resuspension) estimated by comparing settling fluxes measured in surface sediment traps with those measured in bottom traps, were significantly larger (approximately 34% larger) in Lake Honda (LH; 1.18) than in Lake Nueva (LN; 0.88). Our model estimates of resuspension fluxes ( E ) were also ca. 40% larger in LH than in LN, in agreement with the observed focusing factors. The larger resuspension fluxes encountered in LH, in comparison with LN, can mainly be explained by differences in lake morphometry. Still, they could arise from differences in grain size distribution or in benthic algae concentration encountered in the lake sediments. By means of adsorption experiments in the laboratory, we show that resuspension events will have different effects on P-dynamics in LH and LN. While the resuspended material from LH tends to adsorb phosphate (PO 4 3− ), removing it from the water column, in LN the resuspended sediments tend to increase the availability of PO 4 3− in solution. These differences arise from (1) higher concentrations of PO 4 3− in water in LH compared to LN; and (2) larger PO 4 3− adsorption capacity of the LH sediments as a result of the more abundant iron oxyhydroxides and clay.